Frammenti del corpo-voce: le poetesse improvvisatrici fra Sette e Ottocento (ENTHYMEMA, 2022)
The vibrant bodies of the improvisers represented a phenomenon of marked intermediality between the Eighteenth and Nineteenth centuries, loaded with extended cultural values ​​that have been enhanced by recent multidisciplinary research. Rethinked as living documents, as places that is of a performance that is staged of itself in the forms of a continuous dialogue with the public, with tradition, with social conventions, with genres, those inviolate bodies have not yet stopped talking, alongside their timeless eloquence. This article aims to analyse some aspects of the body-voice of the improvvisatrici through literary and iconographic documentary sources, starting, in particular, from some famous portraits made by Angelica Kauffmann to arrive at the celebratory statuary and the memory transmitted by the chronicles of the shows, from the reviews, from the egodocuments, in order to highlight the construction of a public identity inside and outside the scenes.
Keywords: Extemporaneous Poetry; Improvisation; Neoclassicism; Romanticism